2003
DOI: 10.1002/zoo.10094
|View full text |Cite
|
Sign up to set email alerts
|

Splitting suckling data of bottlenose dolphin (Tursiops truncatus) neonates in human care into suckling bouts

Abstract: This study presents a first approach to determine a suckling bout criterion interval (BCI) by applying a log e frequency analysis to a dataset of Tursiops truncatus neonate feeding frequencies. The data were gathered by continuous observation on four calves 15-24 hr a day for the first 14 days postpartum. The study was conducted at the dolphinarium of the Kolma˚rden Wild Animal Park, Kolma˚rden, Sweden. Based on a total of 3,752 individual suckling intervals, a BCI of 107.7 sec was established. The relevance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Tavolga and Essapian [1957] suggested that the mother largely controls the milk release into the mammary sinuses. They, as well as Jacobsen [2001], also described how the mother could control whether or not the calf could achieve a lockon by changing her swimming speed and presenting her nipples. Amundin [1999] and Jacobsen [2001] concluded from their studies that the mother, not the calf, controls the suckling and the subsequent nursing frequency pattern that emerge.…”
Section: Leaving/joining Behavior Before Nursing and Time Interval Bementioning
confidence: 94%
See 4 more Smart Citations
“…Tavolga and Essapian [1957] suggested that the mother largely controls the milk release into the mammary sinuses. They, as well as Jacobsen [2001], also described how the mother could control whether or not the calf could achieve a lockon by changing her swimming speed and presenting her nipples. Amundin [1999] and Jacobsen [2001] concluded from their studies that the mother, not the calf, controls the suckling and the subsequent nursing frequency pattern that emerge.…”
Section: Leaving/joining Behavior Before Nursing and Time Interval Bementioning
confidence: 94%
“…They, as well as Jacobsen [2001], also described how the mother could control whether or not the calf could achieve a lockon by changing her swimming speed and presenting her nipples. Amundin [1999] and Jacobsen [2001] concluded from their studies that the mother, not the calf, controls the suckling and the subsequent nursing frequency pattern that emerge. They suggested that the patterns were a result of the female's behavior and the functioning of her mammaries, e.g., mammary sinus volume and milk ejection.…”
Section: Leaving/joining Behavior Before Nursing and Time Interval Bementioning
confidence: 94%
See 3 more Smart Citations